Multi-center and multi-vendor evaluation study across 1.5 T and 3 T scanners (part 2): T1 and T2 standardization in the ISMRM/NIST MR phantom - Pasini, Siria; Ringgaard, Steffen; Vendelboe, Tau; Garcia-Ruiz, Leyre; Strittmatter, Anika; Villa, Giulia; Raj, Anish; Echeverria-Chasco, Rebeca; Bozzetto, Michela; Brambilla, Paolo; Aastrup, Malene; Hansen, Esben S. S.; et al. (Magnetic resonance materials in physics, biology and medicine, 2025)
Objective To assess multi-site and multi-vendor accuracy, and intra- and inter-scanner variability of T1 and T2 measurements using the ISMRM/NIST System MRI phantom at room temperature. Materials and methods T1 and T2 measurements were acquired using standardized NIST protocols on 13 scanners (1.5 T and 3 T) from 3 vendors at 7 sites and compared with reference values at room temperature. Pearson’s correlation (r) and accuracy error were used for comparison with reference values, while inter-scanner agreement was assessed using the coefficient of variation (CV%). Short-term reproducibility was evaluated using Bland-Altman plots and precision error. Generalized linear mixed models and post hoc tests (α = 0.05) were adopted to compare accuracy and precision across field strengths, vendors, and scanners. T2 measurements were corrected with StimFit toolbox for stimulated echo compensation. Results T1 and T2 measurements had excellent correlation with reference values at both field strengths. Stimfit significantly improved T2 accuracy in the renal range for 9 of 13 scanners. Short-term reproducibility (limits of agreement < 10%) and inter-scanner agreement were good (median CV < 7%) for both T1 and T2 values. Inter-scanner CV was < 5% in the renal range for both parameters. Discussion These findings support the need of scanner evaluation processes to ensure reliable T1-T2 measurements in multi-center MRI studies.
Online veröffentlicht: 17. Mai 2025
Gesehen am 16.09.2025